“Won’t Somebody Please Think of the Children?” The Conservative Creation of a Childhood in Danger in Latin America - Ramírez García, Víctor Hugo (Confluenze. Rivista di Studi Iberoamericani, 2021)
Based on interdisciplinary research on the conservative “gender ideology” trend that has appeared in several Latin American countries in the last five years, this article argues that childhood(s) are at the centre of this trend as captive subjects and hostages of a symbolic struggle. The documentary analysis of different judicial, legal, political or educational elements, focused on three specific cases —Brazil, Peru and Mexico—, allows an examination of sexual difference as an unquestionable truth and of the parental hierarchy as the foundation of the generational power struggle.